The Use of Educational Pictures for Arabic Teaching Belongs to Ministry of Religion Affairs Press and Taha Putra Press/ استخدام الصور التعليمية بين كتاب تعليم اللغة العربية لوزارة الشؤون الدينية وكتاب تعليم اللغة العربية لطباعة طه - Sarifudin; Guergap Aissa (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2021)
This study aims to compare pictures in Bahasa Arab Textbook (Book A) and Ta’limullughah ‘Arabiyah Textbook (Book B). This research includes the type qualitative research. The author uses data collection instruments in the form of interviews and document studies to analyze two selected books. The data collected was analyzed using descriptive analysis techniques, and likert scale. The results of this study indicate that, first, Bahasa Arab Textbook has fewer photographic Pictures than Ta’limullughah ‘Arabiyah Textbook. Second, Ta’limullughah ‘Arabiyah Textbook has pictures in exercise and additional lessons while the Bahasa Arab Textbook does not. Bahasa Arab Textbook has Pictures on istima' while the Ta’limullughah ‘Arabiyah Textbook does not. Third, In terms of drawing attractiveness, Bahasa Arab Textbook fulfill more drawing attractiveness criteria than Ta’limullughah ‘Arabiyah Textbook.